Proposta para criação de uma rede de informação econômica - Queiroz, Suzy de Souza (1977)
Study for the creation of a network on Economics in order to supply the needs of the Nationsl Program for Economic Research (PNPE) cpommunity. Use of the existinf libraries and documentation centers as a cooperative system on an institucional leval. Data obtained through the PNPE-Register of Teachers and Researchs were collected by INPES/IPEA, in 1976 compative analysis of the Pos-Graduate Centers of Economics and of the Research Institution (INPES). through study of the Individual characteristics and trends of the activities of the course, the research, and the literature produced in them. Possibilities pof combining resources in technical and administrative processing toward the goal of improcement and speed in the retrieval and tranfer of interesting information.